PREREQUISITES AND PERSPECTIVES OF THE APPLICATION OF ABSOLUTE IMMUNITY TO ARBITRATORS - Varapnickas, Tadas (Teisė, 2017)
This article analyses absolute immunity of arbitrators from the civil suits, possibilities to apply it as well as its validity. The article examines origins of absolute immunity, explains the advantages and disadvantages of it, analyses whether it would be possible to apply absolute immunity of arbitrators under the Lithuanian law.